Parasitisasi dan Kapasitas Reproduksi Cotesia flavipes Cam. (Hymenoptera: Braconidae) pada Beberapa Jumlah dan Ukuran Larva Chilo sacchariphagus Boj. (Penggerek Tebu Bergaris) (Lepidoptera: Crambidae) di Laboratorium - Poppy Margaretha Siregar; Suzanna F Sitepu; Hasanudin Hasanuddin (Jurnal Agroekoteknologi, 2015)
The objectives of this research was to study the parasitization and reproduction capacity ofCotesia flavipes Cam. (Hymenoptera: Braconidae) on different number and size of larvaeChilo sacchariphagus Boj. larvae (Lepidoptera: Crambidae). The research was conducted at theLaboratory of Sugarcane Research and Development Sei Semayang, Binjai, North Sumatera fromMay until June 2014. This method used Randomized Complete Design with two factors. The firstfactor was numbers of larvae Chilo sacchariphagus (1, 2 and 3) and the second factor was sizeof C. sacchariphagus (small, medium and large) with three replications.The results showed thatsize from larvae C. sacchariphagus significantly effected the percentage of parasititation.The highest percentage of parasititation (77.78%) on big larvae (2-2.5cm) and the lowest (37.33%)on the medium larvae (1.5-2cm). The day of cocoons formed were between 16-18 days. Sex ratio ofmale (41.13%) and female (58.86%) with ratio was 1 : 1.43.Keywords : parasitization, Cotesia flavipes, Chilo sacchariphagus, host size.